THE EFFECT OF INTERNAL MARKETING, ORGANISATIONAL COMMITMENT ON JOB PERFORMANCE IN SPORTS AND RECREATION SERVICES - Fiekri Ilhami Putra; Icha Putra Fadhlillah; Muhammad Iqbal Prihartono (Jurnal Ekonomi Trisakti, 2023)
This study aims to determine whether there is an influence of Internal Marketing, Organisational Commitment on Job Performance in Sports and Recreation Services. The approach used in this research is to use a quantity approach and a simple random sampling methodology. Data were collected through the distribution of online questionnaires, and the results of testing the hypothesis with multiple regression analysis were applied to 90 responses given by respondents. In this study, only one hypothesis is supported. Namely, organisational commitment has a positive effect on work performance. Meanwhile, Internal Marketing does not affect Work Performance. The survey was conducted because the authors wanted to determine whether there was an effect of Internal Marketing, Organisational Commitment on Job Performance in Sports and Recreation Services.